The Requirement to Model Business Process Complexity Measure - Salehah, Hamzah (2004)
Business process is the collection of task and activities that takes one or multiple inputs and create a single or multiple outputs. It covers the people who conduct it, the tools they used to assist them, the production they follow and the flow of material and information between various people, groups and sub-activities. A complex business process should be well managed its complexity so that it could be used as a measure for doing improvement. Business process complexity measure can be described as a type of measure that occur in each item that connected in business process within their different domain that based on their organization goals for performance. To implement a complexity measure for business process, we should refer to the model used. Basically, there should have elements known as requirements that is a capability needed to achieve the goal of complexity measure model development. For that reason, this paper will suggest the several requirements that should have for modeling a business process complexity measure.